Using liveworksheet as an outline teaching platform to evaluate students' listening skills - Hashim, Siti Noor Aneeis; Kanestion, Anita; Bujal, Hanisah; Abdul Kadir, Abdul Halim; Baharudin, Siti Mastura; Faisal, Nur Amalina; Sa’ari, Haziah; Singh, Gurmit (AnKa Publishers, 2022)
This research used a liveworksheet platform to assess students' listening abilities and viewpoints. As a result of the COVID-19 epidemic affecting schools, we need appropriate media, particularly for listening skills, and one of the best venues is liveworksheets. As a result of Liveworksheet's numerous valuable features and its novel, interactive platform, online students are more engaged in assignments that need them to demonstrate their listening abilities. This research employs a quantitative approach, testing survey instruments via questionnaires. A total of 55 kids from Junior High School's 2nd grade participated in this research. Students' listening skills improved significantly after using liveworksheet, as shown by the results of the pre-and post-tests. Fiftyone percent of students strongly agree that listening lessons are essential, 45 percent strongly agree that the liveworksheet is an effective platform, 44 percent strongly agree that the platform needs to be maintained, 43 percent strongly agree that liveworksheets are the expected media, and 40 percent of students strongly agree that liveworksheets are easy to access media for listening skills. According to these findings, students' listening abilities improved as a consequence of using the liveworksheets platform.